2021
DOI: 10.3389/fpls.2021.648841
|View full text |Cite
|
Sign up to set email alerts
|

In planta Genome Editing in Commercial Wheat Varieties

Abstract: Limitations for the application of genome editing technologies on elite wheat (Triticum aestivum L.) varieties are mainly due to the dependency on in vitro culture and regeneration capabilities. Recently, we developed an in planta particle bombardment (iPB) method which has increased process efficiency since no culture steps are required to create stably genome-edited wheat plants. Here, we report the application of the iPB method to commercially relevant Japanese elite wheat varieties. The biolistic delivery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…1d). Collectively, these results demonstrated that the iPB-RNP method is capable of being deployed for in planta genome editing with comparable efficiency to the iPB-DNA method 9 .…”
Section: Mainmentioning
confidence: 78%
“…1d). Collectively, these results demonstrated that the iPB-RNP method is capable of being deployed for in planta genome editing with comparable efficiency to the iPB-DNA method 9 .…”
Section: Mainmentioning
confidence: 78%
“…Generally, winter cultivars are more difficult to transform as they require vernalisation and the transformation rates are lower compared to spring varieties and, as part of the study, we optimised the transformation procedure for them (see Materials and Methods). Since there are only few published examples of genome editing in winter wheat [ 26 , 27 ], our work will be of interest to researchers working on winter wheat transformation and genome editing.…”
Section: Discussionmentioning
confidence: 99%
“…To generate the ta-eif4e and ta-eif(iso)4e lines, we needed to optimise the transformation procedure for the three winter wheat cultivars Cezanne, Goncourt and Prevert (see Materials and Methods). Since there are only few published examples of genome editing in winter wheat (Li et al, 2020;Liu et al, 2021), our work will be of interest to researchers working on winter wheat transformation and genome editing.…”
Section: Discussionmentioning
confidence: 99%